A Challenging diagnosis that eventually results in a life-threatening condition: Addison's disease and adrenal crisis. Issue 12 (29th December 2019) - Joersjö, Philippa; Block, Linda
Abstract : A young man endures many years with classic symptoms of Addison's disease due to difficulties in distinguishing this rare condition, whose features are non-specific and insidious in nature. With all facts on hand, the patient's notable history of psychiatric disorders, namely depression, anxiety and social isolation, as well as signs of extreme fatigue and syncope may well have been caused by a gradual onset of primary adrenal insufficiency. Long delays in diagnosis are not uncommon, as in this case where the actual condition was identified just in time when the patient presented with a life-threatening cardiovascular collapse.